Food safety knowledge, attitude, and practice toward compliance with abattoir laws among the abattoir workers in Malaysia - Abdullahi, Auwalu; Hassan, Azmi; Kadarman, Norizhar; Saleh, Ahmadu; Baraya, Yusha’u Shu’aibu; Pei , Lin Lua (Dove Medical Press, 2016)
Purpose: Foodborne diseases are common in the developing countries due to the predominant poor food handling and sanitation practices, particularly as a result of inadequate food safety laws, weak regulatory structures, and inadequate funding as well as a lack of appropriate education for food-handlers. The most frequently involved foods in disease outbreaks are of animal origin. However, in spite of the adequate legislation and laws governing the abattoir operation in Malaysia, compliance with food safety requirements during meat processing and waste disposal is inadequate. Therefore, the present study was designed to assess the food safety knowledge, attitude, and practice toward compliance with abattoir laws among the workers in Terengganu, Malaysia. Materials and methods: A cross-sectional survey was conducted using simple random sampling technique in the six districts of Terengganu: two districts were used for the pilot study and the remaining four were used for the main study. One hundred sixty-five abattoir workers from the selected districts were interviewed using a structured questionnaire. Results: The mean and standard deviation of knowledge, attitude, and practice scores of the workers were 6.02 and 1.954, 45.16 and 4.496, and 18.03 and 3.186, respectively. The majority of the workers (38.8%) had a low level of knowledge and 91.7% had a positive attitude, while 77.7% had a good practice of compliance. Sex had a significant association with the level of knowledge (P,0.001) and practice (P=0.044) among the workers. The females had a higher level of knowledge than the males, while the males had a better practice of compliance than females. Similarly, knowledge also had a significant (P=0.009) association with the level of practice toward compliance with abattoir laws among the workers. Conclusion: The abattoir workers had a positive attitude and good practice, but a low level of knowledge toward compliance with the abattoir laws. Therefore, public awareness, workshops, and seminars relevant to the abattoir operations should be encouraged.